Finite Element Analysis of Hastelloy C-22HS in End Milling - K., Kadirgama; M. M., Rahman; Ahmad Rasdan, Ismail; R. A., Bakar (Faculty Mechanical Engineering, UMP, 2011)
This paper presents a finite element analysis of the stress distribution in the end milling operation of nickel-based superalloy HASTELLOY C-2000. Commercially available finite element software was used to develop the model and analyze the distribution of stress components in the machined surface of HASTELLOY C-22HS following end milling with coated carbide tools. The friction interaction along the tool-chip interface was modeled using the Coulomb friction law. It was found that the stress had lower values under the cut surface and that it increased gradually near the cutting edge.